Neonization method for stopping, mean excitation energy, straggling, and for total and differential ionization cross sections of CH4, NH3, H2O and FH by impact of heavy projectiles - Miraglia, Jorge Esteban (2014)
Abstract. We propose a neonization method to deal with molecules composed by hydrides of the second row of the periodic table of elements: CH4, NH3,OH2, and FH. This method describes these 10-electron molecules as dressedatoms in a pseudo spherical potential. We test it by covering most of the inelasticcollisional magnitudes of experimental interest: ionization cross sections (total,single and double differential), stopping power, energy loss straggling and meanexcitation energy. To this end the neonization method has been treated withdifferent collisional formalisms, such as the continuum-distorted-wave-eikonalinitial-state, the first order Born, and the shell-wise local plasma approximations. We show that the present model reproduces the different empirical values with high reliability in the intermediate to high energy region. We also include the expansion of the spherical wave functions in terms of Slater-type orbitals and the analytic expression for the spherical potentials. This makes it possible in the future to tackle present neonization strategy with other collisional models.